Single-nucleotide polymorphisms in the IL-4 and IL-13 promoter region in aggressive periodontitis - Gonzales, J. R.; Mann, M.; Stelzig, J.; Bödeker, R. H.; Meyle, J. (Journal of clinical periodontology, 2007)
Introduction: IL‐4 and IL‐13 polymorphisms have been shown to influence the susceptibility to systemic diseases. In this study, possible associations between the IL‐4 −590 C→T, IL‐4 −34 C→T, IL‐13 −1112 C→T and IL‐13 −1512 A→C promoter polymorphisms were investigated in subjects with generalized aggressive periodontitis (AgP) compared with healthy individuals. Material and Methods: Fifty‐eight patients with diagnosis of generalized AgP and 51 matched healthy controls participated in the study. Blood samples were collected and DNA isolated. Molecular analyses were performed by PCR‐RFLP in a blind fashion. Genotype and allele frequencies among study groups were compared using Fisher's exact test (α value: 0.05). Pearson's χ2 test was used for analysis of Hardy–Weinberg equilibrium. Results: The frequency of the IL‐4 −590 T/T and IL‐4 −34 T/T genotypes differed significantly between groups (p=0.05, 0.02, respectively), although the allele frequencies were similar. There was a higher frequency of the IL‐4 −590 T/T and IL‐4 −34 T/T genotypes in patients with AgP compared with controls. The genotype and allele frequencies of the IL‐13 polymorphisms did not differ between groups. Conclusions: This study demonstrated an association between the IL‐4 −590 T/T and IL‐4 −34 T/T genotypes and AgP. Further research is necessary to prove if there is an association of these polymorphisms with AgP, and if the polymorphisms have a functional effect.